Iowa RBA, January 5, 1998 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1998)
Email for the Iowa RBA for January 5, 1998. Highlights include Prairie Falcon, Eurasian Collared Dove, Glaucous Gull, Lesser Black-backed Gull and Thayer's Gull. Epson - sheet feed/flatbed